The aging of China’s population: Perspectives and implications - Quanhe Yang (Asia-Pacific Population Journal, 1988)
Since the late 1970s, China has been making strong efforts to accelerate the pace of modernization. Because the Chinese Government considers poor economic development and rapid population growth to be the main obstacles to modernization, it has emphasised both of those aspects.